FOREIGN BODY INGESTION IN A PEDIATRIC PATIENT - Siljanovski, Hristijan; Jakimovska Dimitrovska, Maja (Македонско лекарско друштво = Macedonian medical association, 2025)
Foreign body ingestion is a common pediatric emergency, often occurring in children between the ages of 6 months and 6 years. This can result in a wide variety of clinical presentations, with approximately 50% of affected children remaining asymptomatic. Early diagnosis and intervention are crucial to prevent complications. Coins are the most frequently ingested objects, followed by toys, batteries, bones, and other small items. Radiological imaging, particularly radiography, is an essential diagnostic tool to locate the ingested object and determine the appropriate management approach.
Keywords: foreign body ingestion; pediatric radiology; coin ingestion; gastrointestinal foreign body; child safety